Adult men’s knowledge and practice about the use of medicinal plants: implications for care - Silva, Silvana de Oliveira (2017)
Objective: to know the knowledge and practices of adult men enrolled in a Family Health Strategy, about the use of medicinal plants. Methodology: Qualitative, descriptive and exploratory research. Adult men who used medicinal plants regularly participated. Data collection through semi-structured interview and non-participant observation and interpretation by analysis of thematic content. Results: The family members between generations transmit the popular knowledge about medicinal plants and the use of plants is related to the relief of specific symptoms. The practice of handling and preparation of medicinal plants differs from scientific recommendations regarding dosage and interaction with other substances. Conclusion: the health professionals included in the Family Health Strategy need to recognize this practice as present in the daily life of adult men and carry out multidisciplinary educational actions based on scientific knowledge to contribute to the use of medicinal plants in a safe way.